PENGARUH PENERAPAN ISO/IEC 17025:2005 TERHADAP KOMPETENSI LABORATORIUM PENGUJIAN BALAI BAHAN PERKERASAN JALAN DI BANDUNG - M. Tranggono (Jurnal Jalan-Jembatan, 2006)
The management of laboratory testing is highly important in achievement of certain level of qualitu standard that will be effected to the accuracy of testing result or their technical competence. Main focus of this study to evaluate the influence of application ISO/IEC 17025 to technical competence of "Laboratorium Pengujian BBPJ (LP-BBPJ)" throught out interlaboratory testing schemes that involve randomly selected sub-samples from a source of material being distributed simultaneously to participating testing laboratories for asphalt testing. After completion of testing from each laboratory, result of testing were collected and analyzed by robust z-scope to give indication of performance of their technical competence. Due to the main focus is LP-BBPJ, then only related data were analyzed by statictic descriptive to fit the generalization of the technical competence result. In general, it was found that te LP-BBPJ has been applied ISO/IEC 17025:2005 consistency. The effect of this application, either it can be provide a good accuracy testing and it can be used as a reference of asphalt laboratory testing due to the result of analyses for asphalt testing are satisfied in general.